2017
DOI: 10.22462/11.12.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

The Dewey monitor: Pulse oximetry can independently detect hypoxia in a rebreather diver

Abstract: _____________________________________________________________________________________________________________________________________________________________________Rebreather diving has one of the highest fatality rates per man hour of any diving activity in the world. The leading cause of death is hypoxia, typically from equipment or procedural failures. Hypoxia causes very few symptoms prior to causing loss of consciousness. Additionally, since the electronics responsible for controlling oxygen levels in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The value of 95% was selected for consistency with Ref. 6 , which determined 95% to be a desirable level to avoid false positives for a SpO2-based hypoxia alarm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of 95% was selected for consistency with Ref. 6 , which determined 95% to be a desirable level to avoid false positives for a SpO2-based hypoxia alarm.…”
Section: Methodsmentioning
confidence: 99%
“… 9 , 10 A previously reported pilot study investigated the utility of a forehead-worn pulse oximeter to detect falling oxygen levels in the rebreather’s breathing loop by measuring the blood oxygen saturation (SpO 2 ) of the diver rather than the partial pressure of oxygen (piO 2 ) inspired from the breathing loop. 6 The pilot study indicated that a forehead-worn oximeter may provide a minimum of 49 s (± 17 s SD) of warning time to the diver independently of the rebreather’s electronics package. However, this pilot study was performed with test subjects in the air rather than immersed in water, and thermal changes in water have been shown to cause delays of up to four minutes for pulse oximeters placed at certain measuring locations.…”
Section: Introductionmentioning
confidence: 99%
“…Another valid parameter is arterial oxygen saturation (SaO 2 ) or the amount of O 2 carried by the hemoglobin in arterial blood, expressed in terms of percentage, which is still measured in arterial blood. The most non-invasive method used is pulse oximetry, especially to detect and monitor for hypoxia by tracking peripheral oxygen saturation (SpO 2 ) [ 10 , 11 , 12 ]. In healthy people resting and breathing at sea level, a value above 95% is considered normal [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota, being emerged as a pivotal transducer of environmental factors, influences to exert effects on the heath and the metabolism of host animals ( 18 20 ), and its composition can be influenced by several environmental extremes, such as hypoxia, heat, and cold ( 21 , 22 ). Hypoxia is a life-threatening environmental factor to most mammals, which leads to loss of consciousness or even death within minutes ( 23 , 24 ). Indeed, even though hypoxia adaptation has been studied for several decades, the relationship between the gut microbiota and hypoxia has been receiving some attention only during the last few years.…”
Section: Introductionmentioning
confidence: 99%